Computational systems biology of epithelial-hybrid-mesenchymal transitions. Issue 3 (June 2017) - Jolly, Mohit Kumar; Levine, Herbert
Abstract: Metastasis accounts for more than 90% of cancer-related deaths, and is fueled by fine-tuned transitions among many cellular phenotypes. Transitions among epithelial (strong cell–cell adhesion, no or little migration), mesenchymal (no cell–cell adhesion, high migration), and hybrid epithelial/mesenchymal (both cell–cell adhesion and cell migration) phenotypes are considered to be a hallmark of metastasis. Recent years have witnessed rapid progress in mapping the regulatory networks underlying these transitions. This progress has enabled the capability to develop computational systems biology models to characterize how various intracellular and extracellular signals can drive these transitions. Here, we discuss how different mathematical models have contributed to elucidating the underlying principles of these transitions and guided further experiments to address key unanswered questions concerning metastasis. Highlights: EMT and MET are not binary; cells can attain hybrid epithelial/mesenchymal state(s). Mechanism-based and data-based computational models can quantify the EMT/MET spectrum. These models can also investigate a role of EMT in other traits such as stemness.